Altered static and dynamic spontaneous brain activity in patients with dysthyroid optic neuropathy: a resting-state fMRI study - Jinling Lu; Hao Hu; Jiang Zhou; Wenhao Jiang; Xiongying Pu; Huanhuan Chen; Xiaoquan Xu; Feiyun Wu (Frontiers in Neuroscience)
PurposeTo investigate static and dynamic brain functional alterations in dysthyroid optic neuropathy (DON) using resting-state functional MRI (rs-fMRI) with the amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo).Materials and methodsFifty-seven thyroid-associated ophthalmopathy (TAO) patients (23 DON and 34 non-DON) and 27 healthy controls (HCs) underwent rs-fMRI scans. Static and dynamic ALFF (sALFF and dALFF) and ReHo (sReHo and dReHo) values were compared between groups. The support-vector machine (SVM) classification method was used to examine the diagnostic performance of the identified models.ResultsCompared to non-DON patients, DON patients showed decreased sALFF in the bilateral lingual gyrus (LING) and right cuneus (CUN), alongside increased sALFF in the bilateral medial part of the superior frontal gyrus, right dorsolateral part of the superior frontal gyrus (SFGdor), and right precentral gyrus. DON patients also exhibited decreased dALFF in the left LING and right CUN, together with increased dALFF in the right orbital part of the middle frontal gyrus and right SFGdor in comparison to non-DON patients. Meanwhile, DON patients had lower sReHo in the right LING, and higher sReHo and dReHo in the right supramarginal gyrus compared to non-DON patients. When detecting DON, the dALFF model showed optimal diagnostic performance (AUC 0.9987).ConclusionDysthyroid optic neuropathy patients exhibited both static and dynamic brain functional alterations in visual, cognitive, and emotion-related brain regions, deepening our current understanding of the underlying neural mechanisms of this disease. Rs-fMRI-based metrics, especially dALFF, may serve as relevant neuroimaging markers for diagnosing DON.